Teachers' informal feedback seeking towards the school leadership team. A social network analysis in secondary schools. Issue 4 (4th July 2019) - Tuytens, Melissa; Moolenaar, Nienke; Daly, Alan; Devos, Geert
Abstract: Teachers' feedback seeking is considered as important for their professional learning. This study aims to investigate which school leaders are sought out for informal feedback by teachers and what leadership characteristics might influence this choice in secondary schools in Flanders, Belgium. Data from 436 teachers of 14 secondary schools are used for social network analysis and multilevel regression analyses. In these schools, the average size of the leadership team is eight, consisting of principals, assistant principals and teacher leaders. Results indicate that the frequency of teachers' informal feedback seeking towards their leadership team is rather low. However, teachers turn the most towards their principals for informal feedback. Multilevel regression analyses show that transformational leadership seems to be the most influential characteristic for this choice. Instructional leadership is only influential for the informal feedback seeking from principals, while transformational leadership shows to be important for all three leadership categories (principal, assistant principals and teacher leaders). The article identifies several pathways for further research to extend our knowledge about informal feedback seeking of teachers in schools. Also for leadership development programmes implications are formulated including the needed attention on the topic of feedback provision for teachers.